2016
DOI: 10.1371/journal.pone.0160815
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Fatigue Resistance and Force Generated by OneShape Instruments during Curved Canal Preparation

Abstract: ObjectivesTo evaluate the cyclic fatigue resistance and the force generated by OneShape files during preparation of simulated curved canals.MethodsSix OneShape files (the test) and six ProTaper F2 files (the control) were subject to the bending ability test. Another thirty files of each type were used to prepare artificial canals (n = 60), which were divided into 3 groups according to respective curvatures of the canals (30°, 60°, and 90°). The numbers of cycles to fatigue (NCF) as well as the positive and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The increase in the curvature of the root canal will result in a dramatic change in the thrust force, which reaches the same conclusion as other researches. 24,25 At the same time, as we can see from Figure 6(c), the increase of diameter and feed rate have led to an increase of torque. But, with the increase of width of root canal, the torque has decreased.…”
Section: Analysis Of the S/n Ratiomentioning
confidence: 54%
“…The increase in the curvature of the root canal will result in a dramatic change in the thrust force, which reaches the same conclusion as other researches. 24,25 At the same time, as we can see from Figure 6(c), the increase of diameter and feed rate have led to an increase of torque. But, with the increase of width of root canal, the torque has decreased.…”
Section: Analysis Of the S/n Ratiomentioning
confidence: 54%
“…In the contrary, Wang et al, (38) found that OneShape files had higher cyclic fatigue resistance than ProTaper Universal (F2) files when files tested in canals with 60° and 90° angle of curvature.…”
Section: Discussionmentioning
confidence: 94%